The regulatory role and mechanism of exosomes in hepatic fibrosis - Yao, Youli; Chen, Da; Yue, Zengchang (Frontiers in Pharmacology, 2023)
Globally, the prevalence and fatality rates of liver disorders are on the rise. Among chronic liver conditions, hepatic fibrosis stands out as a central pathological process. Despite this, approved treatments for hepatic fibrosis are currently lacking. Exosomes, small extracellular vesicles secreted by various cell types, play a significant role in intercellular communication and have emerged as essential mediators in liver fibrosis.In this regard, this review compiles the mechanisms through which exosomes regulate hepatic fibrosis, encompassing diverse targets and signaling pathways. Furthermore, it delves into the regulatory impact of exosomes modulated by natural plant-derived, endogenous, and synthetic compounds as potential therapeutic strategies for addressing hepatic fibrosis.